Pendampingan Pembuatan Laporan Cash Flow dalam Mengelola Keuangan Rumah Tangga di Jalan Siwalan Manyar Gresik - Anisaul Hasanah; Dini Ayu Pramitasari; Bustanul Ulum (Jurnal Pemberdayaan Masyarakat, 2023)
The purpose of this service is to provide knowledge to residents on Jalan Siwalan Manyar regarding making cash flow reports (Cash Flow) in managing household finances, especially for residents of Siwalan Manyar so that expenses are not greater than their expenses. To realize this goal, we are holding a training program entitled "Assistance in creating cash flow reports in managing household finances on Jalan Siwalan Manyar Gresik" namely proposed services for the economic and educational problems experienced by PKK women on Jalan Siwalan Manyar Gresik. The results of this training show that the items most in demand by PKK mothers are investment knowledge with a percentage of 85% and basic personal finance knowledge items with 80%. By embodying the principles of financial planning and decision making, household accounting will produce accurate financial records and reports, and can be used to compare the current month with the previous month so that it can be used as assessment material in the process of making a financial plan for the following month.